Expression of a Tagless Single-Chain Variable Fragment (scFv) of Anti-TNF-α by a Salt Inducible System and its Purification and Characterization - Sain, Avtar; Sen, Priyankar; Venkataraman, Krishnan; Vijayalakshmi, Mookambika A. (Protein and Peptide Letters, 2021)
Background: Anti-TNF-α scFv is gaining acceptance as an effective drug for various diseases, such as rheumatoid arthritis and Crohn’s disease that involve elevated levels of TNF-α. The single-chain variable fragment (scFv) consists of variable regions of heavy and light chains of monoclonal antibodies (mAb). Due to its smaller size, it curbs the mAb’s auto-antibody effects and their limitation of penetration into the tissues during the neutralization of TNF-α. Objective: In this work, a cDNA coding for anti-TNF-α scFv was successfully cloned into a pRSET-B vector and efficiently expressed in an E. coli strain GJ1158, a salt inducible system that uses sodium chloride instead of IPTG as an inducer. Methods: The protein was expressed in the form of inclusion bodies (IB), solubilized using urea, and refolded by pulse dilution. Further, the amino acid sequence coverage of scFv was confirmed by ESI-Q-TOF MS/MS and MALDI-TOF. Further studies on scaling up the production of scFv and its application of scFv are being carried out. Results: The soluble fraction of anti-TNF-α scFv was then purified in a single chromatographic step using CM-Sephadex chromatography, a weak cation exchanger with a yield of 10.3 mg/L. The molecular weight of the scFv was found to be 28 kDa by SDS PAGE, and its presence was confirmed by western blot analysis and mass spectrometry. Conclusion: Anti-TNF-α scFv has been successfully purified in a salt inducible system GJ1158. As per the best of our knowledge, this is the first report of purification of Anti-TNF-α scFv in a salt inducible system from soluble fractions as well as inclusion bodies.
Keywords: inclusion body